(untitled) (Contemporary Journal of Social Science Review, 2025)
This paper assesses changing tendencies in digital linguistic activities in Pakistan based on a corpus analysis of Instagram posts with special consideration of lexical innovation and code-mixing. Based on the dataset of 1,200 public Instagram posts by Pakistani users in 20242025, the study shows new trends in the use of hybrid linguistic expression depending on globalization, technological progress, and local sociolinguistic principles. It was revealed that the English, Urdu, and regional languages have dynamic relations under digitally mediated situations, which demonstrates the creative ways of code-mixing, transliteration, and blending the style by the users. These practices do not just demonstrate identity performance but also allow expressing emotions and communicating with the various audience. Using sociolinguistic theories and analysis of digital discourse, this paper puts Instagram in a new perspective as a space to share images, but it turns out to be a place where identities are negotiated, and languages are innovated.